Laparoscopic Total Mesorectal Excision With Coloanal Anastomosis for Rectal Cancer. Issue 1 (January 2015) - Denost, Quentin; Adam, Jean-Philippe; Pontallier, Arnaud; Celerier, Bertrand; Laurent, Christophe; Rullier, Eric
<x xml:space="preserve">Abstract</x> Objective: Oncologic and functional outcomes were compared between transanal and transabdominal specimen extraction after laparoscopic coloanal anastomosis for rectal cancer. Background: Laparoscopic coloanal anastomosis is an attractive new surgical option in patients with low rectal cancer because laparotomy is not necessary due to transanal specimen extraction. Risks of tumor spillage and fecal incontinence induced by transanal extraction are not known. Methods: Between 2000 and 2010, 220 patients with low rectal cancer underwent laparoscopic rectal excision with hand-sewn coloanal anastomosis. The rectal specimen was extracted transanally in 122 patients and transabdominally in 98 patients. End points were circumferential resection margin, mesorectal grade, local recurrence, survival, and functional outcome. Results: The mortality rate was 0.5% and surgical morbidity rate was 17%. The rate of positive circumferential resection margin was 9% and the mesorectum was graded complete in 79%, subcomplete in 12%, and incomplete in 9%. After a follow-up of 51 months (range, 1–151), the local recurrence rate was 4% and overall survival and disease-free survival rates were 83% and 70% at 5 years, respectively. The continence score was 6 (range, 0–20). There was no difference of mortality rate, morbidity rate, circumferential resection margin, mesorectal grade, local recurrence (4% vs 5%, P = 0.98), and disease-free survival rate (72% vs 68%, P = 0.63) between transanal and transabdominal extraction groups. Continence score was also similar (6 vs 6, P = 0.92). Conclusions: Transanal extraction of the rectal specimen did not compromise oncologic and functional outcome after laparoscopic surgery for low rectal cancer and seems as a safe option to preserve the abdominal wall.